Multi-wavelength brillouin-erbium fiber laser utilizing bismuth-oxide erbium doped fiber incorporating high and low nonlinear fibers - Salem, Ramzia (2011)
Multiwavelength fiber lasers are of great interest in the wavelength division multiplexing systems. To accommodate for the exponential growth in internet, the transmission capacity has to be enhanced in terms of the number of channels. In order to achieve this aim, one approach is to reduce the channel spacing between the wavelengths. The other approach is to increase the gain bandwidth restricted by erbium doped fiber amplifier. Since the bandwidth is dependent on the Er3+ structure in glass material, many fiber amplifiers have been developed to broaden the gain bandwidth. Bismuth-based erbium-doped fiber (Bi-EDF) demonstrates fundamental properties showing broadband emission range and can be doped with Er3+ without experiencing the negative results of ion-quenching and clustering effects compared to silica-based glass allowing the erbium concentration to be more than 3000 ppm. This dissertation presents experimental design and development of multiwavelength Brillouin-erbium fiber laser (MWBEFL) sources operating in the L-band transmission window utilizing 2.49 m Bi-EDF. Three different laser designs have been realized by utilizing stimulated Brillouin scattering (SBS) effect in optical fibers to generate multiple lasers. Two types of special fibers, photonic crystal fiber (PCF) with high nonlinearity and large effective area fiber (LEAF) with low nonlinearity, are being investigated individually. These two types of fibers are then merged together to investigate the laser’s performance parameters. The first design for multiwavelength laser comb comprises of Bi-EDF and 50 m photonic crystal fiber in a ring cavity configuration. This fiber laser is solely pumped by a single 1455 nm Raman pump laser to exploit its higher power delivery compared to that of a single mode laser diode pump. At 264 mW pump power and 1 mW Brillouin pump (BP) power, 38 output channels in the L-band have been realized with optical signal-to-noise ratio above 15 dB and Stokes lines spacing of 0.08 nm. The laser exhibits a tuning range of 12 nm and produces stable Stokes lines across the tuning range between Brillouin pump wavelengths of 1603 and 1615 nm. The tuning range of 12 nm is considered high since very short length, 50 m PCF is used. However, due to the spectral broadening of the laser lines caused by four-wave mixing (FWM) effect associated with high nonlinear fibers, the optical signal-to-noise ratio (OSNR) is degraded and the tuning range is limited to only 12 nm. Another multiwavelength laser comb using 2.49 m Bi-EDF with different lengths of LEAF in a ring cavity configuration has been developed. The Bi-EDF is used as the linear gain medium and LEAF is used as the non-linear gain medium for SBS. Out of the four different lengths, the longest length of 25 km LEAF exhibits the widest tuning range of 44 nm (1576 to 1620 nm) in the L-band at 264 mW pump power and 5 mW Brillouin pump power. In addition, a total of 15 output channels are achieved with total average output power of –8 dBm from this laser structure. All Brillouin Stokes signals exhibit high peak power of above –20 dBm per signal and their OSNR of greater than 15 dB. The Bi-EDF based MWBEFL is also characterized with 22 km Vascade® L1000, another type of LEAF, as the Brillouin gain medium. This fiber generates more Stokes lines than the 25 km LEAF with higher Stokes lines output power. However, the tuning range achieved is 38 nm compared to 44 nm for 25 km LEAF. The third structure of MWBEFL incorporating cascaded PCF and two different lengths of LEAF individually is demonstrated. In this design, the tuning range is enhanced significantly reaching 54 nm from 1566 -1620 nm, at 264 mW pump power and 5 mW BP power, without a trace of self-lasing throughout, utilizing 22 km Vascade® L1000 along with 50 m PCF. Five output channels can be tuned along the whole region of 54 nm. Although this design provides high tuning range, but the number of output channels is reduced. At Raman pump power of 395 mW and 5 mW BP power, up to 9 channels can be widely tuned over 49 nm. The channels exhibit high output power and high stability with average power fluctuation of 0.34 dB over 60 minutes time span. The effect of FWM is reduced thus enhancing the OSNR by 5.2 dB due to the suppression of turbulent waves effect owing to the larger core size in LEAF.